2020
DOI: 10.2174/1871520620666200508090515
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumor Activity of Afatinib in Pancreatic Ductal Adenocarcinoma Cells

Abstract: Background: Pancreatic Ductal Adenocarcinoma (PDAC) is the most common form of pancreatic cancer and leading causes of pancreatic cancer death because of most PDAC patients with advanced unresectable disease at that time, which is remarkably resistant to all forms of chemotherapy and radiotherapy. Objective: PDAC increases the social and patients family burden. However, the PDAC pathogenesis is not identified. We are trying to uncover the underlying mechanism in the future. Methods: In our research, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recently, it has been reported that autophagy contributed to afatinib resistance in pancreatic ductal adenocarcinoma (PDAC). Knocking-down Beclin-1 to block autophagy significantly decreased the half-maximal inhibitory concentration of afatinib in afatinib-resistant cells [ 14 ]. Importantly, we found that inhibition of autophagy, either by combined treatment with autophagy inhibitors or by Atg5 siRNA transfection, increased afatinib-induced apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that autophagy contributed to afatinib resistance in pancreatic ductal adenocarcinoma (PDAC). Knocking-down Beclin-1 to block autophagy significantly decreased the half-maximal inhibitory concentration of afatinib in afatinib-resistant cells [ 14 ]. Importantly, we found that inhibition of autophagy, either by combined treatment with autophagy inhibitors or by Atg5 siRNA transfection, increased afatinib-induced apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies revealed that stimulation of autophagy was involved in the induction of afatinib resistance in pancreatic ductal adenocarcinoma (PDAC). Furthermore, blocking autophagy via knockdown of Beclin-1 distinctly decreased the IC50 value of afatinib in resistant cells [ 14 ], and Xiangxiang Hu et al demonstrated that afatinib caused autophagy in lung adenocarcinoma with activating EGFR mutations. Importantly, in vivo and in vitro assays demonstrated that suppression of autophagy with chloroquine (CQ) and 3-methyladenine (3-MA) markedly heightened afatinib-induced cytotoxicity, indicating that autophagy serves as a protective response in lung adenocarcinoma cells treated with afatinib [ 15 ].…”
Section: Introductionmentioning
confidence: 99%